Health Benefits and Medicianl Value of Honey - Sara Marshall; Liwei Gu; Keith R. Schneider (EDIS, 2015)
Honey has been used for medicinal purposes for thousands of years. It is rich in sugars such as glucose and fructose, but it also contains small amounts of vitamins, minerals, amino acids, and antioxidants such as phenolic acids and flavonoids. These nutrients help to make honey a unique, natural health product. Its market niche as a health product is growing, and current research supports the potential of honey as a medicinal product. This 3-page fact sheet describes health aspects of honey deriving from the floral source and color, beneficial compounds, anti-microbial properties, and anti-inflammatory properties. Written by Sara Marshall, Liwei Gu, and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition, April 2015.